(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Organisms produce a large variety of biologically active peptides and have high inhibitory activity against other organisms that cause spoilage and spoilage of many foods. Lactic acid bacteria are considered one of the most important single-celled organisms that are characterized by their ability to produce biologically active peptides. They are of great importance because they are useful and widespread. Most types of lactic acid bacteria can produce bioactive peptides that inhibit peptides bactericidal bioactive bacteria (bacteriocins), which can control the growth of pathogenic bacteria and the formation of (biofilm), this mechanism by these bacteria not only generates the free amino acids needed by bacteria but also It produces a variety of peptides, some of which have biological activities. These are called “bioactive peptides (BAPs) and are interesting from a nutrition and health care perspective, as they have many functions such as antimicrobial antioxidant, anticholesterol and anti-hypertension. Their activities vary according to the strain. Bacteria in terms of containing proteinase enzymes, which leads to a large variety of proteolytic activities. Through this study, Lactobacillus delbrueckii JKD5 bacteria were isolated from local yogurt in the city of Basrah in southern Iraq. It was isolated and purified under anaerobic conditions, its morphology was studied and biochemical tests were conducted for it. It was genetically diagnosed and registered in the NCBI Gene Bank with the number OM278543.1 or original Purely under the name Lactobacillus delbrueckii JKD5 .Partial purification was carried out by precipitation with ammonium sulphate at 75% saturation, centrifugation at 10000 rpm for 10 minutes, then the bacterial filtrate was taken, then membrane osmosis was carried out using dialysis bags, and the peptides were extracted and purified by HPLC and ÄKTA pure devices to reach the total purification. A characterization study was conducted for the produced peptide and it showed that it has a molecular weight of 6.5 kDa and was stable at 60 and 80 °C for 60 minutes, which indicates that the peptides can withstand high temperatures in the sterilization process, which is one of the very important processes in food production. It retains its effectiveness at pH 3 and 5. The activity of the peptide produced from the antibacterial isolate JKD5 was characterized and examined against two types of bacterial strains, one positive and the other negative for Gram stain. They are Bacillus cereus and Escherichia coli.